Contamination With Fumonisin B and Deoxynivalenol Is a Threat to Egg Safety and Contributes to Gizzard Ulcerations of Newborn Chickens - Wang, Yihui; Quan, Hongkun; Li, Xiaohui; Li, Qiang; Haque, Md Atiqul; Shi, Qin; Fu, Qiang; He, Cheng (Frontiers in Microbiology, 2021)
Fumonisin B and other fumonisins, deoxynivalenol , and zearalenone are mycotoxins present at high levels of contamination in poultry diets, and threating to the sustainability of the poultry industry and egg safety for consumers. However, residual mycotoxins in breeder eggs, and their effect on chicken progeny and gizzard ulcerations are remain unclear. To unveil mycotoxin contaminations from daily diets to breeder eggs, 293 poultry feed samples were collected from three large-scale poultry provinces across Norther and Southern China. Average levels of 1628±4.36μg/kg of FB1, 593±11.16μg/kg of DON, 69±9.21μg/kg of ZEN, 52±7.33μg/kg of OTA, and 24±5.85μg/kg of AFB1 were found in feedstuffs and poultry diets. In terms of residual mycotoxins in breeder eggs, FB1 and DON contaminations dominated residues in egg albumens and yolk samples. Out of 221 breeder eggs, the average residues of FB1 in albumen are 320.6±10.12μg/kg (Hebei), 420.2±10.98μg/kg (Guangdong), and 549.4±10.27 (Guangxi), respectively. Moreover, higher residual DONs were determined in Guangdong and Guangxi provinces compared in Hebei province. ZEN, ochratoxins A and aflatoxin B1 contamination at low levels were found in the above the samples collected from three provinces. Based on residual mycotoxins in breeder eggs, SPF embryonated eggs aged 11 days were inoculated into albumen with different doses of FB1, FB2 or a combination of FB1 and DON or combination of FB1 with FB2 and FB3. Lower hatching rate was observed in the chicken progenies with 24μg of FB1 and combination of 24μg of FB1 and 0.1μg of DON compared to in other treatments. Moreover, typical gizzard ulcerations with hemorrhagic lungs were observed in the progeny of breeder eggs were observed post inoculation of 24μg of FB1 and synergetic inoculation of FB1 and DON. Finally, residual FB mycotoxins were detected in the gizzards and in the lungs of the progenies. Based on the above evidences, feed-borne FB1 and DON are dominated mycotoxins in breeder eggs and threating to food security using breeder eggs as Trojan horse. More important, the residuals of FB1 alone and combination of DON contamination are associated with low hatch rate and gizzard ulcerations in chicken progenies, hampering sustainable development perspectives of poultry industry.